PRODUCTIVITY SHOCKS, FOREIGN DIRECT INVESTMENT, AND CAPITAL TAXES - Zirgulis, Aras (Ekonomika, 2015)
The present study deals with the effect that productivity and capital taxes have on foreign direct investment through a panel consisting of 41 countries utilising the GMM system on a dynamic spatial model. Evidence reveals that an increase in the domestic capital tax rate leads to less FDI inflows, and higher levels of domestic productivity growth lead to less FDI inflows. Foreign competition did not have a significant effect on domestic FDI inflows.
Keywords: FDI; productivity shock; capital taxes; tax competition